Cretaceous evolution of the Andean margin between 36°S and 40°S latitude through a multi‐proxy provenance analysis of Neuquén Basin strata (Argentina). (10th February 2016) - Di Giulio, Andrea; Ronchi, Ausonio; Sanfilippo, Alessio; Balgord, Elizabeth A.; Carrapa, Barbara; Ramos, Victor A.
Abstract: During the Cretaceous, the Neuquén Basin transitioned from an extensional back‐arc to a retroarc foreland basin. We present a multi‐proxy provenance study of Aptian to Santonian (125–84 Ma) continental sedimentary rocks preserved in the Neuquén Basin used to resolve changes of sediment drainage pattern in response to the change in tectonic regime. Sandstone petrology and U–Pb detrital zircon geochronology constrain the source units delivering detritus to the basin; apatite U–Pb and fission track dating further resolve provenance and determine the age and patterns of exhumation of the source rocks. Sandstone provenance records a sharp change from a mixed orogenic source during Aptian time ( ca . 125 Ma), to a magmatic arc provenance in the Cenomanian ( ca . 100 Ma). We interpret this provenance change as the result of the drainage pattern reorganisation from divergent to convergent caused by tectonic basin inversion. During this inversion and early stages of contraction, a transient phase of uplift and basin erosion, possibly due to continental buckling, caused the pre‐Cenomanian unconformity dividing the Lower from Upper Cretaceous strata in the Neuquén Basin. This phase was followed by the development of a retroarc foreland basin characterised by a volcanic arc sediment provenance progressively shifting to a mixed continental basement provenance during Turonian‐Santonian (90–84). According to multi‐proxy provenance data and lag times derived from apatite fission track analysis, this trend is the result of a rapidly exhuming source within the Cordillera to the west, in response to active compressional tectonics along the western margin of South America, coupled with the increasing contribution of material from the stable craton to the east; this contribution is thought to be the result of the weak uplift and exhumation of the foreland due to eastward migration of the forebulge.